Mass and Contact Time of Activated Carbon Treatment to Adsorption Efficiency for Coffee Processing Wastewater - Elida Novita; Arthanti Yulia Admaja; Hendra Andiananta Pradana (Jurnal Keteknikan Pertanian, 2021)
Coffee is one of the crops that has a high economic value. Wet or dry coffee processing will produce waste that can pollute the surrounding environment. Environmental impact caused by coffee wastewater in the form of water that becomes cloudy with dark color. The treatment can be done using the adsorption method. The purpose of this research was to determine the efficiency of the best activated carbon mass and the optimum contact time in the adsorption process on the treatment of coffee processing wastewater. The mass of activated carbon used in each sample is 5 grams, 10 grams, and 15 grams with contact time of 60 minutes, 90 minutes, and 120 minutes.The parameters were examined consist of turbidity and colour. The best treatment is mass of activated carbon of 15 g and interaction of 60 minutes. By using a different mass and the time of contact in adsorption can decrease the characteristics of coffee processing wastewater that is in the turbidity parameter yields a efficiency of 89.58% and in color parameters reached 83.86%.